Investigating the Relationship of Body Mass Index, Diet Quality, and Physical Activity Level between Fathers and Their Preschool-Aged Children - Vollmer, Rachel L.; Adamsons, Kari; Gorin, Amy; Foster, Jaime S.; Mobley, Amy R. (Journal of the Academy of Nutrition and Dietetics, 2015)
Diet quality and physical activity are two important factors in determining a child’s risk for obesity. In early childhood, parents may serve as role models for these behaviors. However, few studies have examined associations of a father’s body mass index (BMI), dietary intake, and physical activity with his preschool-aged child. The purpose of this study was to examine relationships between fathers’ and children’s body weight, diet quality, and physical activity. This cross-sectional study included one-on-one interviews with fathers (n=150) of preschool-aged children conducted by a trained interviewer (a registered dietitian nutritionist). To be eligible, biological fathers (n=150) of preschool-aged children (aged 3 to 5 years) were required to regularly eat at least one meal per week with their child and be able to read or speak English. They could be of any race, ethnicity, income, or education level. During the interview, diet quality was assessed using a single 24-hour recall and the Healthy Eating Index-2010. Physical activity was assessed using the Pre-Physical Activity Questionnaire. Height and weight for each father and child were also measured. BMI and BMI z scores were calculated for fathers and children, respectively. Linear regression was used to test relationships between fathers’ and children’s body weight, diet quality, and physical activity while controlling for income level, race, and ethnicity. Overall, the findings revealed that there were significant, positive relationships between father–child weight status (β=.03; P=0.05), overall diet quality (β=.39; P<0.0001), and weekday (β=.27; P=0.002) and weekend (β=.62; P=0.001) vigorous physical activity. These results suggest that there are relationships between fathers’ and children’s BMI z score, dietary intake, and physical activity level. Future research should consider the inclusion of fathers in obesity prevention programs for young children.